Inside SQL server 2005 tools - Raheem, Michael (Addison Wesley Professional, 2006)
Direct from Microsoft Insiders: the Complete Hands-On Guide to SQL Server 2005's Powerful Tools! Microsoft SQL Server 2005's high-powered management tools can dramatically improve DBA productivity and effectiveness. Now there's a comprehensive guide to SQL Server 2005's toolset, straight from the Microsoft team that created it. This book covers the entire toolset in unprecedented depth, guides database professionals in choosing the right tools, and shows them how to use various tools collectively to solve real-world problems. The authors present "how-to" solutions and never-before-published tips for SQL Server 2005 installation, upgrades, configuration, authoring, schema design, development, deployment, optimization, troubleshooting, and more. Coverage includes Â Understanding how SQL Server 2005 tools differ from their predecessors Â Leveraging the new Business Intelligence Development Studio and Management Studio to accomplish dozens of common tasks Â Improving security by reducing the "surface area" you expose Â Executing queries with the new Query Editor and SQLCMD query tools Â Optimizing with the revamped SQL Server Profiler and Database Engine Tuning Advisor Â Scheduling maintenance tasks with the SQL Server Agent Â Monitoring with the Activity Monitor, SQL Server Agent, and other tools Â Moving data efficiently and reliably with Integration Services Â Using SQL Server's new e-mail tool, Database Mail Â Managing replication in complex distributed environments Â Mastering SQL Server's Analysis Services' OLAP and Data Mining tools Â Using Notification Services 2.0, Reporting Services, and more Â Extending functionality using underlying APIs and the included CD-ROM's sample code. MICHAEL RAHEEM is the senior product manager of the Microsoft SQL Server team and led the design and implementation of several SQL Server tools, such as SQL Server Management Studio, Database Mail, Upgrade Advisors, and Surface Area Configuration. He currently leads the SQL Server enterprise marketing efforts including high availability, scalability, and performance. DIMA SONKIN is development lead in the SQL Server Tools group responsible for SQL Server Agent, SMO, DMO, SQL Profiler, Database Engine Tuning Advisor, Database Mail, SQLMail, SqlCmd, and OSQL. THIERRY D'HERS is the lead program manager on Microsoft's SQL BI Analysis Services team and has spent five years designing and specifying Analysis Services tools. KAMI LEMONDS is the documentation ...